(untitled) (Research, Society and Development, 2025)
Ruthenium (Ru) is a second transition series metal known for its versatility in terms of applications. A member of the iron (Fe) family, together with osmium (Os), it has varied uses, from participation in metal alloys to application in various drug prototypes. Ruthenium (Ru) has a very rich coordination chemistry, which also contributes to its variability of uses, including as a catalyst. The aim of this article is to discuss fundamental aspects of ruthenium chemistry and some of its applications. One strategy that has already been considered, but that requires further advances, consists of using ruthenium (Ru) complexes in combination with other conventional drugs (Lin, 2018). It is possible that highly promising results will arise from this treatment tactic and new advances in the fight against cancer and infectious diseases could be achieved.